Smart Polymeric Wound Dressing for Treating Partial-Thickness Burns: A Preliminary Preclinical Study on the Porcine Model - Dmitry Beylin; Josef Haik; Erik Biros; Rachel Kornhaber; Michelle Cleary; Moti Harats; Daniel Cohn; Yair Sapir; Ori Weisberg (MDPI AG, 2023)
Several so-called "smart" dressings are available for burn injuries to promote faster wound healing, and this technology has recently reported substantial advancements. However, the selection of an appropriate dressing for partial-thickness burns requires consideration of several crucial elements, including exudate management, conformability, antimicrobial properties, ease of application and removal, patient comfort, and cost-effectiveness. This preliminary feasibility study uses a porcine model to test the INTELIGELS product (Smart Bandage) for partial-thickness burns treatment. Artificially made wounds, mimicking partial-thickness burns, were assessed in two studies with and without antimicrobial additives, where wounds were randomly assigned to the experimental group treated with Smart Bandage and two control groups treated with a simple saline gauze dressing or Aquacel® products with and without silver additives. In addition, all dressings were evaluated for their ability to reduce wound size, quantified by histological analysis using punch biopsies. This study demonstrates comparable healing properties of Smart Bandage and Aquacel® dressings that are superior to the simple saline gauze dressing. The superiority is demonstrated by better regeneration, less inflammation of the epidermis and dermis, and better dermis remodeling with more granulation tissue maturation within the wound area when Smart Bandage/Aquacel® dressings are applied as compared with the simple gauze dressing.